Les pratiques paysagistes à l’épreuve du film de recherche - Chris Pividori (Projets de Paysage)
Over the last few decades, landscape architecture has emerged in France as an alternative to urban planning, which is all too often limited to functionalist recipes. Landscape architects have endeavoured to produce spaces that integrate not only the ecological, social and cultural specificities of territories, but also the sensitive dimension of people’s relationship with their environment. As a methodological exercise, this article examines such spaces in the light of research films. The Bordeaux metropolitan area serves as an example, demonstrating the gradual integration of landscape and landscape design practices within public policy in a changing context where social expectations regarding landscape architects are multiple and sometimes in contradiction with one another. The initial results underline the need to go beyond a narrative of professional life which is unable to characterise the professional and personal ethical practises involved. The aim here is to examine the capacity of a non-academic account, the filmed and commented professional trajectory and the resulting research film, to offer a clear insight into landscape practices and the values that underpin them.